Juridical Overview of the Use of Smart Contracts in Indonesia as a Form of Artificial Intelligence Development - Muhammad Rizqon Baihaiqi; Siti Ummu Adillah; Dahniarti Hasana (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
Apart from the problems in terms of data security in the midst of blockchain-based business development in Indonesia, it turns out that another problem in smart contracts is that the use of Smart Contracts in Indonesia is actually still a discourse among legal experts regarding the validity of smart contracts. The aims of this research are: a) To find out and analyzeimplementation of the use of smart contracts in Indonesia; b) To know and analyzeobstacles in implementing smart contracts in Indonesia and their solutions; c) To know and analyzelegal remedies that can be taken in the event of a dispute between the parties in the smart contract; d) To find out examples of deeds inthe use of smart contracts in Indonesia as a form of artificial intelligence development.